Data bank development and organization for automatic selection of tools and cutter conditions for grinding - Todić, Velimir (Journal of Production Engineering, 1991)
Automatic tools selection and selection of cutter conditions during technology processes projection and optimization, represent significant contribution to whole efficiency increasing of technological preparation for production. Development and organization of data bank for tools and cutter conditions requires application of all rules on which is high-quality and reliability use of these information system are based. This data bank enables automatic tools selection and selection of cutter conditions. Rules which enable permanent data bank for cutter conditions enlarge with new data are the most important. These new data are in harmony with possibilities which are defined by cutter tools, new mechanical materials, mechanical treatment conditions and contemporary manufacturing systems. In the paper, the rules and the logic of tools and cutter conditions data bank for grinding development, organization and use are shown. This data bank is the part of technological data bank which enables selection of these technological elements on the interactive principle.